2013
DOI: 10.1128/mcb.01008-12
|View full text |Cite
|
Sign up to set email alerts
|

ARID1a-DNA Interactions Are Required for Promoter Occupancy by SWI/SNF

Abstract: Every known SWI/SNF chromatin-remodeling complex incorporates an ARID DNA binding domain-containing subunit. Despite being a ubiquitous component of the complex, physiological roles for this domain remain undefined. Here, we show that disruption of ARID1a-DNA binding in mice results in embryonic lethality, with mutant embryos manifesting prominent defects in the heart and extraembryonic vasculature. The DNA binding-defective mutant ARID1a subunit is stably expressed and capable of assembling into a SWI/SNF com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
125
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 76 publications
3
125
0
Order By: Relevance
“…ARID, a conserved feature of SWI/SNF, can be found in the Swi1 subunit of yeast SWI/SNF and in the ARID1a and ARID1b subunits of human SWI/SNF or BAF complexes. Recent data showed that ARID in human SWI/SNF is required for binding to promoters (98). Although the SWIRM domain in SWI/SNF binds to DNA, some SWIRM domains in other complexes appear to have lost this ability (99).…”
Section: Nucleosome Recognition: Dna Binding Domainsmentioning
confidence: 99%
“…ARID, a conserved feature of SWI/SNF, can be found in the Swi1 subunit of yeast SWI/SNF and in the ARID1a and ARID1b subunits of human SWI/SNF or BAF complexes. Recent data showed that ARID in human SWI/SNF is required for binding to promoters (98). Although the SWIRM domain in SWI/SNF binds to DNA, some SWIRM domains in other complexes appear to have lost this ability (99).…”
Section: Nucleosome Recognition: Dna Binding Domainsmentioning
confidence: 99%
“…This results in a decrease in promoter occupancy by SWI/SNF, and defects in cardiovascular development. 18 Since missense mutations involving the ARID domain are present in human cancers, it raises a possibility that ARID-DNA interactions are essential for the tumor suppressor function of ARID1A and loss of such interaction (due to mutations) abolishes its tumor suppression function.…”
mentioning
confidence: 99%
“…Mutation of the HSA domain prevents GR-mediated BRG1-dependent transcription. Similar, mutations within ARID domain induce defects in SWI/SNF function [ 105 ]. Mutation of V1068G in ARID1A is also homozygous lethal.…”
Section: Arid1a Mediates Glucocorticoid Signalingmentioning
confidence: 96%